Distance learning in higher education during coronavirus (covid-19) outbreak - Khalil, M.; Afifi, M.; El-Nahal, W. (SPC Journal of Education, 2020)
When E-Learning is not a choice but the salvation for proceeding in education across the globe. In this paper, we spotlight on the challenges facing the higher education systems during the COVID-19 pandemic. The impact of the COVID-19 crisis on students and higher education institutes are discussed to clarify the available technological opportunities that can be used to address students’ needs. A Case Study is presented in this work to discuss the role of the E-learning in the international pandemic outbreak.